Potential value and cardiovascular risks of programmed cell death in cancer treatment - Yue, Tian; Zheng, Dezhi; Yang, Jiali; He, Jian; Hou, Jun (Frontiers in Pharmacology, 2025)
Programmed cell death (PCD) is equally important for maintaining overall homeostasis as it is for cell proliferation. The dynamic balance between cell proliferation and PCD promotes the body’s continuous self-repair and self-renewal, thus achieving cellular homeostasis. However, when this balance is disrupted, such as through unrestricted cell proliferation or the inhibition of PCD, tumors may occur. Moreover, this inhibition of cell death is considered a major cause of tumor development and a key factor contributing to the poor efficacy of many tumor treatments. Nowadays, with the discovery of an increasing number of PCD modalities, such as necroptosis, pyroptosis, autophagy, ferroptosis, and cuproptosis, PCD has broken the traditional classification of “apoptotic necrosis.” It is also an evolutionary necessity to prevent systemic damage caused by blocking a single cell death pathway. A systematic study of PCD may provide new insights into the origin of malignant tumors, the sensitivity of normal and malignant cells to treatment, and the development of treatment resistance. However, treatment regimens that act on PCD all pose significant cardiovascular risks, including excessive apoptosis of cardiomyocytes, cardiac rhythm abnormalities, cardiac remodeling, and myocarditis, among others. Currently, research on cardiovascular risks in tumor treatment is still incomplete. In this review, we describe different types of cell death processes and their roles in tumorigenesis. At the same time, we also discuss the basic and clinical applications of PCD in tumor pathogenesis, prevention, and treatment, as well as the known or potential cardiovascular risks. This provides a theoretical basis for the continuous progress of PCD-based tumor treatments.